Partial life cycle of pygidiopsis australis Ostrowski de Nuñez, 1996 (digenea: heterophyidae) in Venezuela. - Díaz, Marcos Tulio; Gómez, Erika; Bashirullah, Abul; Guilarte, Del Valle (Revista Científica de la Facultad de Ciencias Veterinarias, 2014)
Â Partial life cycle of Pygidiopsis australis Ostrowski de Núñez was elucidated from encysted metacercariae which was found in the cranial cavity, musculature and abdominal cavity of the naturally infected freshwater fish, Anablepsoides hartii from El Naranjal, Montes Municipality, Sucre State, Venezuela. Metacercariae were fed to rats and chickens experimentally, and adult trematodes were recovered from the small intestines of the experimental hosts, 5-18 days after infection. Descriptions of metacercariae and adult from both naturally and experimentally infected hosts are provided. These adult parasites were compared with the closely related species of Pygidiopsis Looss, 1907, such as: P. ardea, P. australis, P. genata, P. marivillae, P. anterouteria and P. himantopae, and it was concluded that the species is undoubtedly P. australis, which was also reported from chickens and mice in Argentina. However, the metacercariae are showing slight differences in the structure of the cyst wall, the site of infection and the shape of excretory bladder, while variation in number of digitiform pockets in the gonotyl of adults, could be due to geographical and intraspecific variations.